Прийняття рішень в умовах функціонування процесно – орієнтованої системи управління якістю - Хімічева, Ганна Іванівна; Махмуров-Дишлю, Андрій Араїкович; Дімова, Надія Іванівна (Eastern-European Journal of Enterprise Technologies, 2009)
This article offers new ways for typical decisions making concerning the enterprise activity in terens of the process-oriented quality management system.